READING ALOUD PERIODICALLY TOWARDS PRONUNCIATION OF NON-ENGLISH MAJOR STUDENTS - Dhanan Abimanto (Universitas Muhammadiyah Kalimantan Timur, 2020)
This research aims to know about the effectiveness of reading aloud periodically method in assisting the English pronunciation problem made by non-English major students. To measure the effectiveness of the method, the researcher used quasi-experimental research. The researcher took the data from first semester students of the non-English department (students of the Transportation study program). To analyze the data, the researcher used two analyses, which are non-statistical and statistical analysis. Based on the data, the researcher found that in the pre-test, before giving the treatment, students still made some mistakes in English pronunciation. After giving the treatment, students showed the progress in their English pronunciation. There was an increase between the pre-test and the post-test about 21,33 in score or t-test calculation, t count > t table = 10,718>3,12 with 32,53% mispronunciation made by students after giving the treatments 10 times. It showed that the method of reading aloud was effective to help in improving students’ English pronunciation. Besides, the researcher found that the reason for students’ problems in pronunciation after interviewing students was the familiarity to use English in daily activities and the influence of their habit reading the word in the Indonesian language.